As Medianeras em Buenos Aires. O terceiro alçado como elemento de composição no espaço urbano - João Pedro Mesquita Amorim (2015)
The sidewalls are a common element in the urban image of different cities.It appears as an ephemeral element, however, in the period of time when thereis no building in the next lot, it acquires a vital influence on the image producedin the public space. Constant amendments to town planning regulations havegiven the sidewalls the value of a main facade, because of its continuity, size andexposure concerning to the street.Buenos Aires, city of study of this thesis, develops itself through thereticular structure with juxtaposed lots, maintaining the colonial appearance.Although, initially, the development has been done in size, quickly the centralarea densified, emerging the city by exploring the vertical. Being this structureprone to speculative power, in its narrow lots, the diverse plannings allowed animpulsive building construction, giving this way a multiple character to its blocks,where the alternating height is a constant. This situation allows, in a clear way,the appearance of the sidewalls, confronting the users who walk around the cityevery day. The sidewalls becomes a witness of the building evolution history,showing precarious habitability conditions which boosts, although illegally, theopening of gaps by its inhabitants. The city, based on a uniform structure, bygrowing, proposes an heterogeneous and specific lecture of Buenos Aires.The reflection developed in this work about the sidewalls, was madepossible by the lived experience in the city, in the exchange programme asstudent at the Faculty of Architecture, Design and Urbanism of Buenos Aires.The approach to the city's architecture, which allowed an understanding of thepossibilities of action having in mind this pre-existence, was provided by thepossibility of carrying out an internship at the Adamo-Faiden studio.